Transmisi Nilai Karakter Tigel Tarei dalam Pembelajaran Seni Tari - Tri Sartika Rini; Agung Kurniawan; Amelia Hani Saputri (Jurnal Seni dan Pembelajaran, 2020)
The purpose of this research is to find out and describe how the process of the character value transmission of tigel tarei in dance art learning at Senior High School 3 Bandar Lampung. This research uses symbol, character value and transmission theory. The method of this research was the field method and literary. The data resource of this research is in the form of direct interviews with the speakers; cultural, art and culture teachers, seven of tenth grade students, books, papers and ten of tigel tarei movements. The data collecting techniques that used on this research are observation, documentation, and interview. The results of this research showed that the analysis toward the transmission process of character education values in tigel tarei based on fifteen character education values the researcher found five characters education value, they are character education value of life view, integrity, prudent, responsibility, and respectful.Masalah penelitian ini adalah melihat serta mendeskripsikan proses transmisi nilai karakter tigel tarei dalam pembelajaran seni tari di SMA Negeri 3 Bandar Lampung Penelitian ini menggunakan teori simbol, teori nilai karakter dan teori transmisi. Metode yang digunakan adalah metode lapangan dan kepustakaan. Sumber data dalam penelitian ini adalah berupa wawancara langsung terhadap narasumber seperti budayawan, guru seni budaya, tujuh orang siswa kelas X, buku-buku, paper dan sepuluh ragam gerak tigel tarei. Tehnik pengumpulan data yang digunakan yakni observasi, dokumentasi, dan wawancara. Hasil penelitian menunjukkan bahwa hasil analisis terhadap proses transmisi nilai-nilai pendidikan karakter yang terdapat dalam tigel tarei berdasarkan lima belas nilai pendidikan karakter peneliti menemukan lima nilai pedidikan karakter yaitu, nilai pendidikan karakter pandangan hidup, tangguh, bijaksana, tanggung jawab, dan malu.